Vindfällning, tillväxt och plantuppslag i en 13-årig granskärm i Medelpad - Tjernell, Tomas (2007)
The interest for alternative forest regeneration methods increased significantly during the 1990´s after 50 years dominance of the clear-cutting system (Holgén & Hånell 2000). One reason for this was that clear-cutting was being more and more questioned by different envi-ronmental organizations and because the forest sector for economical reasons wanted to find cheaper ways to regenerate forests. In the beginning of the 1990´s two shelterwood experi-ments were established in a joint effort by Svenska Cellulosa Aktiebolaget (SCA) and the Dept of Silviculture, Swedish University of Agricultural Sciences (SLU). The experiments include various forms of cutting and shelterwood densities and represent productive spruce forests in central and north Sweden (Roggsjön in the province of Medelpad and Skikkis-jöberg in the province of Västerbotten, respectively ). The experiment next to Roggsjön has been reported earlier in three MSc theses, and is also the focus of this thesis.